Trabalho docente na educação básica em Vitória/ES - Lievore, Sue Elen (2013)
This Master's thesis is to analyze the conditions of teachers' work in the Municipal city of Vitória, state of Espírito Santo. The study developed integrates the research "The teaching in Basic Education in Brazil ", coordinated by the Study Group on Education Policy and the Teaching Profession, initiated by researchers at the University of Minas Gerais (GESTRADO/UFMG). In the Espírito Santo, the survey was coordinated by the Center for Studies and Research in Educational Policy ( Nepe ), which completed the data collection in 2009 and devoted himself to investigate the teaching in their constitutive dimensions, identifying the actors , the they do and under what conditions the work is done in schools of Basic Education of public and contracted. Besides enabling the understanding of the process of educational reform in teaching, the national survey aimed to support the development of public policies in Brazil. The development of the dissertation was done through the analysis of survey data collected in the national survey, the focus groups of units teaching subjects, as teachers, childhood education assistants and interns. Furthermore , it was analyzed by means of semi-structured interviews, focus group managements education in the sphere of the Municipal Education . The research, without pretending to exhaust the subject, concludes that, on the one hand , teaching in the city of Vitoria , has been deeply affected by the new forms of regulation settled in decentralized actions, making the core of the school management, for other hand, increases job control with the deployment of the evaluation scale. In addition , the worker has experienced teaching processes of precarious labor relations and employment, a breakdown of the educational work more complex and intensified . Therefore, the Municipal Vitoria brings strong elements that characterize the new forms of regulation practiced nationwide